퇴화 쉘요소를 사용한 원통형 복합재 패널의 비선형 좌굴후 현상해석 - 조희근(Hee Keun Cho) (한국생산제조학회지, 2018)
In this study, the post - buckling analysis of cylindrical panel of isotropic material and composites was investigated. The arc-length nonlinear analysis method has been used for the analysis of post-buckling phenomena where snap-through and snap-back phenomenon occur. In this study, a method to find bifurcation point in buckling analysis using arc-length method is presented. The bifurcation point of the buckling was found in the cylindrical shell structure of isotropic material to ensure the reliability of the current approach. The bifurcation buckling point was successfully calculated with composites having extremely high structural instability. The formulations, mathematical model and analysis procedures and boundary conditions proposed in this study can be used as important data for the unstable buckling analysis of other structures. KCI Citation Count: 0